2015
DOI: 10.5958/2394-4196.2015.00020.5
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-containing Mouthwash and Oral Cancer Risk: A Systematic Review

Abstract: The aim of this article is to assess any possible risk of oral cancer with increased usage of alcohol-based mouthwashes and to provide relevant information regarding the safety of using alcohol-containing mouth rinses. Materials and Methods: Several controversial studies regarding the prolonged use of such mouthwashes containing >25% alcohol causes oral cancers, have been reviewed and undertaken. Analyzing the number of studies done till date, it showed debatable views on the use of alcohol-containing mouthwas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(60 reference statements)
0
1
1
Order By: Relevance
“…A general reason for this is that difference in experimental design and animal model beside the limitation for time of exposures mouthwashes. These results reinforced by previous work revealed that no sufficient evidence to argue the correlation between mouthwashes and oral cancer [30,32]. In contrast, some authors reported that the risk of oral cancer might increase with patients experienced with both alcohol and smoking in respective to the intensity and duration of exposure [33].…”
Section: Discussioncontrasting
confidence: 38%
“…A general reason for this is that difference in experimental design and animal model beside the limitation for time of exposures mouthwashes. These results reinforced by previous work revealed that no sufficient evidence to argue the correlation between mouthwashes and oral cancer [30,32]. In contrast, some authors reported that the risk of oral cancer might increase with patients experienced with both alcohol and smoking in respective to the intensity and duration of exposure [33].…”
Section: Discussioncontrasting
confidence: 38%
“…The principle design and development of electronic apex locators (EALs) date back to research undertaken by Suzuki in 1942. [16,17] He found that electrical resistance between the periodontium and oral mucous membrane in dogs was a constant value.…”
Section: Introductionmentioning
confidence: 99%